2004
DOI: 10.1142/s0218216504003020
|View full text |Cite
|
Sign up to set email alerts
|

Markov Trace on the Yokonuma–hecke Algebra

Abstract: It is proved that the Yokonuma-Hecke algebra supports a Markov trace.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
108
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(109 citation statements)
references
References 6 publications
0
108
0
1
Order By: Relevance
“…It is easily verified that the elements e i are idempotents in Y d,n (u) [Ju,Lemma 4]. Also, that the elements g i are invertible, with (2.4) g…”
Section: Computation Formulas In the Iwahori-hecke Algebramentioning
confidence: 97%
“…It is easily verified that the elements e i are idempotents in Y d,n (u) [Ju,Lemma 4]. Also, that the elements g i are invertible, with (2.4) g…”
Section: Computation Formulas In the Iwahori-hecke Algebramentioning
confidence: 97%
“…Juyumaya [Ju2] has shown that the following set is a basis for the Yokonuma-Hecke algebra Y d,n (u):…”
Section: A Basis For the Yokonuma-temperley-lieb Algebramentioning
confidence: 99%
“…, t n are the generators of (Z/dZ) n (recall that Y d,n (u) is a quotient of (Z/dZ) n ⋊ B n ). Juyumaya [Ju2] has shown that, starting with the standard basis B IH of the Iwahori-Hecke algebra H n (u) (case d = 1), one can obtain naturally a basis B YH for the Yokonuma-Hecke algebra Y d,n (u) in the following way:…”
Section: Introductionmentioning
confidence: 99%
“…Note that in the transition from (13) to (14) the partition set π changes from all partitions of L to only partitions of L for which L 1 and L 2 are in different subsets. The equality in (14) follows from the equality in (13) once this difference in partitions is appreciated. Hence, using (14) and also (12), we obtain:…”
Section: A Closed Formula For H[h]mentioning
confidence: 99%
“…The equality in (14) follows from the equality in (13) once this difference in partitions is appreciated. Hence, using (14) and also (12), we obtain:…”
Section: A Closed Formula For H[h]mentioning
confidence: 99%